Yogi Berra, Forrest Gump, and the discovery of Listeria actin comet tails - Portnoy, Daniel A. (The American Society for Cell Biology, 2012)
In 1988, eminent cell biologist Lew Tilney and newly appointed Assistant Professor of Microbiology Dan Portnoy met at a picnic and initiated a collaboration that led to a groundbreaking paper published in Journal of Cell Biology entitled “Actin filaments and the growth, movement, and spread of the intracellular bacterial parasite, Listeria monocytogenes.” The paper has been cited more than 800 times, the most of any publication in the careers of both investigators. Using an electron microscope from the Sputnik era, they assembled a stunning collection of micrographs that illustrated how L. monocytogenes enters the host cell and exploits a host system of actin-based motility to move within cells and into neighboring cells without leaving the host cell cytosol. This research captured the imagination of cell biologists and microbiologists alike and led to novel insights into cytoskeletal dynamics. Here, Portnoy provides a retrospective that shares text from the original submission that was deleted at the time of publication, along with reviewers' comments ranging from “It is really just a show and tell paper and doesn';t have any meat” to “the finding will have major impact in cell biology and in medicine. Potentially, the paper will be a classic.”